(3gOjI GdUYdhc aj TQM JMaI Gdedhcs - (3eMeQe Hf eMeO Hf MSf, J HYO (B1010 (3g`s ((3eQYTs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj LYd bdhH GdYdeGA eQGjG LeGd eYGf GdgOGjI CeG HYO ajbhd GdYHO GdabjQ CHh GddjK GdeMQe Hf eMeO Hf GdYGQa Hf GdMSf GdRjdj deG cfJ CPGcQ cJGH JMaI Gdedhc SCdfj HYV GdWdHI Cf CTQMgG TQMG jaSQ eNajGJg (B-- (3hSejJg gOjI GdUYdhc aj TQM JMaI Gdedhcs
(3BNQgG (B:s
(3bGd (B: (3HCj TjA JMUd GdSYGOI GdCNQhjI hGdHGbjI aCLGH Hbhdg (B: (3hSYGOI GdBNQI EfeG JMUd HJbhi (B( (3cPG (B) (3Gddg hcCf bGFdG (B: (3bGd heG GdJbhi aCLGH (B: (3GdJbhi GLJfGH eMGQeg hgj (B- (3Cj GdJbhi (B- (3hUjI Gddg JYGdi dLejY GdCees
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 284s
(3eYLe GdeDdajf (B3 / 17s
(3EjVGM Gdecfhf (B2 / 727s
(3gOjI GdYGQajf (B2 / 5s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs